The Primitive Traces of the Bhojpuri Language - Thakur, Gopal (Nepalese Linguistics, 2024)
Bhojpuri, a Neo Indo-Aryan language originated from Madhyadesha, now parts of Nepal and India, and also spread worldwide, has a long history of origin and evolution. But it has little been known about its primitive traces in contemporary writings. Siddha and Nath saints are said to have started first but little evidently. The Avahattha literature of Damodar, Jyotirishwar and Vidyapati is nearly untouched. Therefore, this paper is an effort to present its primitive traces empirically from different sources in Apabransha and Avahattha literature from Siddhas till Vidyapati. Though it is in brief, it verifies its origin and evolution.